Fast Charging All Solid‐State Lithium Batteries Enabled by Rational Design of Dual Vertically‐Aligned Electrodes. (13th September 2020) - Gao, Xuejie; Yang, Xiaofei; Adair, Keegan; Liang, Jianneng; Sun, Qian; Zhao, Yang; Li, Ruying; Sham, Tsun‐Kong; Sun, Xueliang
Abstract: The slow charging limitations of all‐solid‐state lithium batteries (ASSLBs) have significantly limited their practical application. Thus, significant improvement of the rate performance and development of fast charging ASSLBs is crucial for the commercialization of these systems. However, poor Li + transport kinetics and Li dendrite formation under high charging current densities have inhibited their capabilities. To tackle these issues, the design of dual vertically‐aligned electrodes (DVAEs) is proposed to accelerate Li + transport and suppress Li dendrite formation. At the anode side, the vertically‐aligned Li (VA‐Li) anode with lithiophilic micro‐walls enables lateral growth of Li deposits rather than perpendicular to the electrode surface, thus preventing dendrite penetration through the separator. In addition, the 3D vertically‐aligned structure in both VA‐Li and vertically‐aligned‐LiFePO4 (VA‐LFP) enables enhanced Li + transport due to lower tortuosity and faster Li + transport kinetics. Benefitting from the rational design, VA‐Li symmetric cells can operate for 300 h at a current density/capacity of 3 mA cm −2 /3 mAh cm −2, while short‐circuiting is observed after 87 h for bare Li cycled at only 0.5 mA cm −2 (capacity: 0.5 mAh cm −2 ). Moreover, a fast‐charging ASSLBs assembled with DVAEs demonstrates a high capacity of 89.4 mAh g −1 after 2000 cycles at 4C. Abstract : A dual vertically‐aligned electrodes (DVAE) structure with well‐controlled microscale features is proposed to suppress Li dendrite growth and facilitate Li + transport concurrently. Based on this concept, a fast‐charging all‐solid‐state Li‐LiFePO4 battery assembled with DVAEs demonstrates a high capacity of ≈90 mAh g −1 after 2000 cycles under a high current density of 4C.